Muscadine grape skin extract inhibits prostate cancer cells by inducing cell-cycle arrest, and decreasing migration through heat shock protein 40. Issue 1 (January 2019) - Ignacio, Diane N.; Mason, Kimberly D.; Hackett-Morton, Ezra C.; Albanese, Christopher; Ringer, Lymor; Wagner, William D.; Wang, Paul C.; Carducci, Michael A.; Kachhap, Sushant K.; Paller, Channing J.; Mendonca, Janet; Li-Ying Chan, Leo; et al.
Abstract: Previously we demonstrated that muscadine grape skin extract (MSKE), a natural product, significantly inhibited androgen-responsive prostate cancer cell growth by inducing apoptosis through the targeting of survival pathways. However, the therapeutic effect of MSKE on more aggressive androgen-independent prostate cancer remains unknown. This study examined the effects of MSKE treatment in metastatic prostate cancer using complementary PC-3 cells and xenograft model. MSKE significantly inhibited PC-3 human prostate cancer cell tumor growth in vitro and in vivo . The growth-inhibitory effect of MSKE appeared to be through the induction of cell-cycle arrest. This induction was accompanied by a reduction in the protein expression of Hsp40 and cell-cycle regulation proteins, cyclin D1 and NF-kBp65. In addition, MSKE induced p21 expression independent of wild-type p53 induced protein expression. Moreover, we demonstrate that MSKE significantly inhibited cell migration in PC-3 prostate cancer cells. Overall, these results demonstrate that MSKE inhibits prostate tumor growth and migration, and induces cell-cycle arrest by targeting Hsp40 and proteins involved in cell-cycle regulation and proliferation. This suggests that MSKE may also be explored either as a neo-adjuvant or therapeutic for castration resistant prostate cancer.